Solidarity Economy and the Commons - Esteves, A. (RedPES - RIPESS Workshop Series, 2021)
Solidarity economy approaches regenerative development from a political economy perspective. Since community-based solutions and shared management towards production and consumption are valued as key concepts, it could be said that it is committed to fostering economic democracy. Solidarity economy also promotes the resilience of social and natural systems by focusing on the scaling, political organization and institutional recognition, through government and regulatory support, of economic practices based on reciprocity, redistribution and householding. These include, among others, those based on traditional economic knowledge, reproductive work and the economy of care. Its ultimate goal is to reconcile economic and social goals, as well as promote the resilience of territories, by promoting the self-organization and self-determination of citizens within Community Led Initiatives such as cooperatives, community-based currencies, microcredit systems and alternative commercialization networks such as short food supply chains. The socio-ecological design approach frames regenerative development from a biocentric and institutionalist perspective, based on weaving cross-sector, multi-stakeholder collaborations for the regeneration of ecosystems. The goal is to redraw economic and political borders along ecological lines and according to principles of decentralization, participatory democracy and cooperation within and among political units. Its strategies are based on the application of biomimicry-based, holistic sets of design principles such as permaculture, agroforestry and traditional ecological knowledge to promote ecosystem regeneration through decarbonization of energy supply, restoration of natural cycles and relocalization of supply chains. Given their limited ability to produce endogenous capital, Community Led Initiatives tend to be dependent on external resources. Public support of Community led Initiatives tends to promote trust in public institutions by reducing the risk of policy failure due to lack of information on the specificities of place. However, a well-balanced policy is needed to guarantee proper conditions for participatory processes and community planning.